Pengaruh Media Video Edukasi Pre Operasi dengan General Anestesi terhadap Tingkat Kecemasan Pasien di Poli Bedah Mulut - Fujillah, Reza Zikri; Laut, Deru Marah; Restuning, Sekar; Fatimah, Siti; Hariar, Addys Rino (Jurnal Terapi Gigi dan Mulut, 2025)
Preoperative anxiety is a psychological condition that occurs prior to surgical procedures, particularly among individuals who have never undergone surgery. This condition is characterized by excessive fear and worry arising from the perception of a threat to personal safety. One approach that can be used to reduce preoperative anxiety is the use of educational video media. This study aimed to examine the effect of preoperative educational videos with general anesthesia on anxiety levels among patients at the Oral Surgery Clinic of Persahabatan General Hospital, Jakarta. A quasi-experimental design with a pretest–posttest two-group design was employed. The sample consisted of 40 participants, divided equally into an intervention group (n = 20) and a control group (n = 20), selected using purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), and data were analyzed using the Wilcoxon test. The results showed that prior to the intervention, 55% of patients in the intervention group experienced moderate anxiety, while 50% of patients in the control group experienced severe anxiety. After receiving the educational video, 65% of patients in the intervention group demonstrated a reduction in anxiety to a mild level, whereas 40% of patients in the control group who received verbal education remained in the severe anxiety category. Statistical analysis revealed a significant difference in anxiety levels before and after the intervention (p-value = 0.000 < 0.05). These findings indicate that preoperative educational videos with general anesthesia are effective in reducing patient anxiety.